Resepsi Fungsional Al-Qur’an dalam Tradisi Keagamaan Lokal: Studi atas Tradisi Roah Kemalik pada Masyarakat Rembiga, Nusa Tenggara Barat - Muhammad Helmi Anshori; Abdul Muhaimin; Aulul Azmi; Ahmad Fathoni (Al-Qudwah)
This article aims to examine how the Rembiga community in West Nusa Tenggara receives and interprets the verses of the Qur’an within the Roah Kemalik tradition, which is deeply embedded in their social and cultural life. The Roah Kemalik tradition developed from the spread of Islam by figures such as Sunan Prapen and Ratu Ambiya and consists of rituals involving the recitation of Qur’anic verses believed to offer protection from disasters and calamities. This study employs a qualitative approach with a descriptive analytical method to elucidate the meanings and social functions of this tradition. The research questions addressed in this study are as follows: First, how is the Qur’an understood by the Rembiga community within the Roah Kemalik tradition? Second, in what forms is the reception of the Qur’an manifested in this tradition? The study concludes that the Rembiga community regards the Qur’an as sacred and deserving of sanctification. This tradition also serves as a process for the transmission and transformation of knowledge and practices that have existed since the arrival of Islam on Lombok Island. Generally, they interpret the Qur’an as a form of tafa’ul (a sign of good fortune); consequently, the meanings that emerge do not always align logically with the original intent of certain verses. The Roah Kemalik tradition is also grounded in several hadiths of the Prophet that legitimize the practice, which has been inherited and preserved by community authorities. This study affirms that the Roah Kemalik tradition is a dynamic social construct that harmonizes Islamic teachings with local culture, thereby shaping the religious identity of the Rembiga community to this day.